KEPERSEPSIAN ZAKAT PENGURANG PAJAK TERUTANG DI KOTA MAKASSAR - M. Wahyuddin Abdullah (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2015)
The aim of this study was to obtain empirical evidence muzakki perception plus a taxpayer of zakat deduction from taxable income and tax payable zakat deduction. Hypothesis testing is done by using a non-parametric statistical tests, the Wilcoxon signed ranks test to determine the significance of equation (difference) and the rank ordering of the average score of two independent groups of the same population. Methods of sampling using purposive sampling totaling 157 respondents in the city of Makassar. The results showed that the taxpayer muzakki plus perceive charity as a deduction from taxable income to charity as a deduction from the tax payable is significantly different, and better perceive (agree) to charity as a deduction from the tax payable. This study implicates renew zakat and tax regulations by treating zakat deduction of tax payable.